Segmental Absence of Intestinal Musculature in a Child with Type IV Ehlers-Danlos Syndrome - Nicole Zeky; Celia Short; Brent Keith; Randall D. Craver; Jessica A. Zagory (MDPI AG, 2021)
Patients with vascular Ehlers-Danlos syndrome (vEDS) have a defect in the formation of type III collagen. This defect puts patients at risk of vascular rupture, uterine rupture, and bowel perforations. The segmental absence of intestinal musculature is a rare histopathologic finding, wherein there is a lack of a muscularis propria layer in the intestinal wall. Although typically documented in the literature in neonates or adults, it can be seen in children of other ages. This is a case report of a patient who exhibits both rare entities, which has not been described in the literature to date.